Analysis of Airflow Patterns and Pressure Distribution Characteristics on Cars with Variations of Under Front End Tilt Angle - I Made Brahmantiar Pranam Dewa (HM Publisher, 2023)
The airflow across the underbody of the car will affect the lift and drag of a car. Part under front end car vehicle is one of the factors in the car that causes drag and also lift. This research was conducted to determine the airflow pattern and pressure distribution characteristics, such as static pressure, dynamic pressure, and pressure coefficient, which affect the performance of the test vehicle with variations in the angle of the under-front end. Experimental testing was carried out on 4 specimens, namely car vehicles with variations in tilt angles under front end 0°, 5°, 10°, and 15° inside the wind tunnel with a speed of 5.47 m/s. The results showed that the under front end of the 0° tilt angle is an area with low pressure, where the lift that occurs is relatively smaller than the under front end area which varies the angle of inclination. However, pressure fluctuations experienced by an angle of 10° are more stable than 0°.